Management of digital contents in multiple displays - Henriques, Bruno Filipe Maia (2021)
With the generalized use of systems for digital contents dissemination arises the opportunity for implementing solutions capable of evaluating audience reaction. This dissertation reflects the implementation of one of those solutions. To this end, the development involved adapting a previously functional digital signage system. In this sense, digital cameras were paired to the content display terminals in order to capture information from the area in front of them. Using computer vision technologies, the terminals detect, in real time, people who appear in the cameras’ field of view, and this information is communicated to a server for data extraction. On the server, methods are used to perform face and emotion recognition, and also to extract data indicating the position of the head, which allows the calculation of an attention coefficient. The data is stored in a relational database, and can be consulted through a web platform, where they are presented associated with the contents corresponding to the moment of their capture and extraction. This solution thus allows the evaluation of the impact of the digital contents presented by the system.